Applications of a modified palatal roll flap in peri-implant soft-tissue augmentation - A case series - Mihir Raghavendra Kulkarni; Purva Vijay Bakshi; Abhishek Somanath Kavlekar; Srinath Lakshman Thakur (Wolters Kluwer Medknow Publications, 2017)
Abrams's palatal roll technique has been used extensively to augment peri-implant soft tissues in the maxillary esthetic zone and has seen numerous modifications. An adaptation of the palatal roll technique is described here and its simplicity of application in three different scenarios is demonstrated. At second-stage implant surgery, a partial thickness initial incision followed by a palatal subepithelial dissection at the site of implant was done and a connective tissue graft with a buccal pedicle was obtained. The graft was rolled under the buccal flap and allowed to heal with the support of a healing abutment. The graft healed uneventfully and provided excellent contours of tissues around the implant. The procedure demonstrated good results for augmentation of a buccal ridge deficiency, for covering exposed and unsightly implant fixtures and was also done with a papilla preservation incision. In addition, a second surgical site to obtain the connective tissue graft was avoided.